Increased Monocyte Procoagulant Activity Independent of the Lupus Anticoagulant in Patients with Systemic Lupus Erythematosus - de Prost, D; Ollivier, V; Ternisien, C; Chollet-Martin, S (Thrombosis and Haemostasis, 1990)
Monocytes can play a role in the activation of coagulation via increased procoagulant activity (PCA). We investigated the level of monocyte PCA in 19 patients with systemic lupus erythematosus (SLE), given the high rate of thrombotic events in this condition. Nine of these subjects also presented the lupus anticoagulant (LA). The PCA generated by patient monocytes was significantly higher than control values and was identified as tissue factor-like. Moreover, the number of monocytes with membrane-associated D dimer, a parameter whieh we have shown to be correlated with the PCA expressed in vitro by endotoxin-activated monocytes, was also significantly increased. Serum from both groups of patients (i.e. SLE and SLE + LA) stimulated the generation of PCA by control monocytes. By contrast, purified IgG from both patient groups had the same effect as control IgG on PCA generation by control monocytes. The nature of the stimulating agent in the serum was not identified. In conclusion, increased monocyte PCA may account for the increased incidence of thrombosis in SLE patients, although other, superimposed, factors would appear to exist in SLE + LA patients, given the higher incidence of thrombosis in this subgroup.